2018
DOI: 10.1190/geo2017-0169.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of saturation on seismic dispersion in shales — Laboratory measurements

Abstract: Previous studies found a significant increase of acoustic velocities between seismic and ultrasonic frequencies (seismic dispersion) for shales, which would have to be taken into account when comparing seismic or sonic field data with ultrasonic measurements in the laboratory. We have executed a series of experiments performed with a partially saturated Mancos shale and a Pierre shale I in which the influence of water saturation on acoustic velocities and seismic dispersion was investigated. The experiments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 51 publications
5
26
0
Order By: Relevance
“…It was recently suggested that in shales it might be related to a local flow of bound water at grain contacts (Szewczyk et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It was recently suggested that in shales it might be related to a local flow of bound water at grain contacts (Szewczyk et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…21). The dispersion mechanisms are not fully understood yet but it may be related to local flow of bound water at grain contacts (Szewczyk, Holt and Bauer 2018).…”
Section: Static Versus Dynamic Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…() and Szewczyk et al . (). This seeming discrepancy in the results obtained on different samples implies that variations in the elastic properties of shales with changing hydration states are driven by multiple competing phenomena.…”
Section: Introductionmentioning
confidence: 97%
“…Vernik and Nur 1992). The elastic moduli of shales have been measured at different hydration states (Vales et al 2004;Wild et al 2015;Ghorbani, Zamora and Cosenza 2009;Szewczyk, Holt and Bauer 2018). Vales et al (2004) reported that the drying of Tournemire shale resulted in a decrease in ultrasonic P-wave velocity propagating perpendicular to the bedding plane, V P (0°), and had no effect on the velocity of a P-wave propagating along the bedding, V P (90°).…”
mentioning
confidence: 99%